COMPARATIVE ASSESSMENT OF POTATO SPECIES IN THE PERM REGION CONDITIONS - N. V. Chukhlantsev; D. S. Fomin (Овощи России, 2018)
Potatoes in all categories of farms in the Permskii Krai occupy 41.3 thousand hectares, in agricultural enterprises – 4.5 thousand hectares, with an average yield for 2014-2016 of 13.9 t / ha. The Permskii Krai there are all the prerequisites for obtaining high yields of potatoes. One of them is potato seed production. Variety, one of the important tasks of seed production, without it, with the ever-increasing need for new universal varieties that combine preservation of the original qualities for as long as possible, i.e. high stable productivity, early yield accumulation, good culinary and technical qualities (starchiness, good keeping quality, etc.) with resistance to the most harmful diseases, pests and adverse environmental conditions cannot be dispensed with. The purpose of research: the identification of promising varieties of potatoes, highly productive, in the Perm region. Investigations were carried out in 2011-2016 at the central experimental field of the Perm Agricultural Research Institute Branch of Perm Federal Research Center of Russian Academy of Science. In the collection nursery, 33 varieties of three groups of precocity were tested. A comparative assessment of potato varieties by yield and economic characteristics is presented. Promising potato varieties for cultivation under the conditions of the Perm Territory were identified in the group of early maturing: Albatross, Nandina, Latona, medium-early varieties: Irbit, 428- 05, Bravo, Miner, Amur. The varieties Crisper, Lukoshko, Bafana were the best in selected indicators in the mid-season group. Comparative assessment of potato varieties according to yield and economic characteristics is presented; studies were carried out at the Perm Agricultural Research Institute Branch of Perm Federal Research Center of Russian Academy of Science in the soil and climatic conditions of 2011-2016. Promising potato varieties for cultivation under the conditions of the Permskii Krai were identified in the group of early maturing: Albatross, Nandina, Latona, medium-early varieties: Irbit, 428-05, Bravo, Miner, Amur. The varieties Crisper, Lukoshko, Bafana were the best in selected indicators in the mid-season group.